Improvement of Power Quality in a Three-Phase System Using an Adaline-Based Multilevel Inverter - Das, Soumya Ranjan; Ray, Prakash K.; Sahoo, Arun Kumar; Balasubramanian, Karthik; Reddy, Gaddam Sanjeeva (Frontiers in Energy Research, 2020)
The existences of harmonics in the power distribution system (PDS) are treated as the most serious issues that affect the stability and reliability. Therefore, active power filter (APF) plays an important role in PDS to compensate the harmonics for improvement in power quality (PQ) and to keep the total harmonic distortion (THD) below 5% as per IEEE-519 standard. In this paper, a three phase four wire (3P-4W) multi-level inverter (MLI) based APF is proposed to overcome the shoot-through effect (STE) and reduce the distortions in supply current. The control of voltage source inverter (VSI) is achieved using Adaline based LMS (A-LMS) algorithm with hysteresis current controller. The proposed filter using A-LMS technique is compared with the conventional recursive least square (RLS) algorithm. A-LMS approach mainly operated for maintaining the dc link voltage of MLI which follows the principle of capacitor energy and reduces the total harmonic distortion (THD) under different load variation. The performance of MLI under different load conditions is designed, developed and validated by using MATLAB/Simulink environment and the preeminent features are established.